NICKEL SULFIDES IN PYROXENITE FROM LANGHOVDE, LUTZOW-HOLM BAY, EAST ANTARCTICA - マツバラ, サトシ; モトヨシ, ヨウイチ; MATSUBARA, Satoshi; MOTOYOSHI, Yoichi (National Institute of Polar Research, 1988)
P(論文) Nickel sulfides occur as minute grains in a pyroxenite xenolith enclosed in a garnet-biotite gneiss from Langhovde, Lutzow-Holm Bay, East Antarctica. They include pentlandite, millerite, violarite and Ni-bearing pyrite in the decreasing order of appearance. The Ni/Fe ratio in pentlandite is high and that in violarite is so variable that reaches Fe (Fe, Ni)_2S_4 with Fe>Ni. Cobalt is exclusively found in violarite. The mode of occurrence and mineral assemblage of the pyroxenite indicate it to have been derived from an ultramafic igneous rock probably corresponding to an ultramafic component of a tectonic melange. departmental bulletin paper